2007
DOI: 10.1111/j.1600-6143.2007.01945.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined Double Lung–Liver Transplantation for Cystic Fibrosis Without Cardio‐Pulmonary By‐Pass

Abstract: Sequential bilateral single lung-liver transplantation (SBSL-LTx) is a therapeutic option for patients with end stage lung and liver disease (ESLLD) due to cystic fibrosis (CF). A few cases have been reported, all of them were performed with the use of cardiopulmonary by-pass (CPB). We performed SBSL-LTx in three young men affected by CF. All the recipients had respiratory failure and portal hypertension with hypersplenism. Along with lung transplants, two patients received a whole liver graft and one an exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
(28 reference statements)
0
14
0
Order By: Relevance
“…Patients with both severe respiratory failure and advanced liver cirrhosis as a result of CFLD are often excluded from consideration of sole lung transplantation or else are offered combined lung–liver transplantation (9). This is largely based on the assumption that CF patients with cirrhosis would be unable to survive the perioperative period and/or develop hepatocellular failure following lung transplantation.…”
mentioning
confidence: 99%
“…Patients with both severe respiratory failure and advanced liver cirrhosis as a result of CFLD are often excluded from consideration of sole lung transplantation or else are offered combined lung–liver transplantation (9). This is largely based on the assumption that CF patients with cirrhosis would be unable to survive the perioperative period and/or develop hepatocellular failure following lung transplantation.…”
mentioning
confidence: 99%
“…In rare cases combined liver and lung transplantation has been performed, but the risk of perioperative complications is high and larger series are not available [180, 181]. In one small series the overall survival of those receiving a combined liver and lung transplantation was 70% at one and three years [181].…”
Section: Other Topicsmentioning
confidence: 99%
“…66 Patients with both severe respiratory failure and advanced liver cirrhosis are most often either offered combined lung-liver transplantation or excluded from transplantation; very few are considered for LT alone. 67 This is based on the assumption that these patients would be unable to survive the perioperative period or would develop hepatocellular failure. However, it has been demonstrated that post-transplant lung function and survival are not different between patients with or without CFLD who undergo LT alone.…”
Section: Liverd Is E a S Ementioning
confidence: 99%